Examining the relationships between supply, demand, and environmental policies for science and technology innovation using a system simulation model - Meirong Zhou; Wenhao Huang; Abbas Mardani (Journal of Innovation & Knowledge (JIK), 2023)
The development of science and technology has been increasingly linked with the implementation of science and technology innovation (STI) policies with important strategic significance for promoting national and regional innovation. In actual implementation, many types of STI policies are often combined for a joint effect; however, existing studies tend to focus on the effect of a single policy. The system simulation method can break through the limitations of traditional methods in model assumptions and establish a model that is as close to reality as possible. Notably, it is unusual to use the system simulation method to investigate STI policies. Using a system simulation model, this study conducts a detailed analysis to examine the complex causal relationships of STI systems and study the impact and mechanism of STI policy from a systematic perspective. This study quantifies various STI policies, establishing a simulation model to reflect the dynamic behavior of the regional STI policy system. The empirical results demonstrate that when a single type of policy is examined, the STI supply policy has the most significant impact on promoting STI and economic development. When various STI policies are combined, the combination of supply and demand policies has the greatest promotional effect on STI and economic development, whereas the combination of demand and environmental policies has the least promotional effect on STI and economic development. The results also show that the combined effect of various STI policies is not based on the simple addition of the effects of various policies, as there is an apparent synergy phenomenon in the combined STI effects. This study contributes to the existing literature and provides practical insights for policymakers and policy enthusiasts to understand the relationships between STI supply, demand, and environmental policies to advance policy effectiveness and promote sustainable development.
Keywords: 650; Experiment design; Policy effect; Policy scenario; Science and technology innovation; System simulation